Effects of Tremella fuciformis -Derived Polysaccharides with Different Molecular Weight on D-Galactose-Induced Aging of Mice - Donghui Luo; Xiaofei Liu; Jingjing Guan; Guili Jang; Yanglin Hua; Xinfei Zhang; Xiaofei Xu (Polish Journal of Food and Nutrition Sciences)
The structure-bioactivity relationship of Tremella fuciformis polysaccharides (TFPs) in anti-aging in vivo is rarely reported. In the present study, a purified TFP, named HM, mainly composed of mannose, fucose, xylose, and glucose in a molar ratio of 4.14:0.98:0.81:0.62, was obtained from the fruiting body of T. fuciformis . Subsequently, two differentially degraded TFPs, named MM and LM, respectively, were prepared by a combined method of ultrasonic irradiation (US) and H 2 O 2 treatment. Their structural properties, scavenging activities against free radicals in vitro , and anti-aging effects on D-galactose-induced aging of mice were determined. The average molecular weight of HM, MM, and LM was 58.3×10 6 , 4.68×10 6 , and 3.14×10 5 Da, respectively. All three TFPs were devoid of triple helix conformation and exhibited concentration- and molecular weight-dependent scavenging activity against radicals. The TFPs markedly relieved skin aging, effectively attenuated oxidative stress, and significantly decreased inflammation in D-galactose-induced aging mice. MM exhibited the best anti-aging effect among the TFPs. Additionally, TFPs partially restored the alterations in pH and the total content of short-chain fatty acids (SCFAs) in the colon but exhibited various impacts on the content of the individual SCFAs. These findings would provide rational guidance for a better application of TFPs in anti-aging foods and expand our understanding of the structure-function relationship of mushroom polysaccharides.